2023
DOI: 10.3390/ijms24076751
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Response of TmToll-3 Following Systemic Microbial Infection in Tenebrio molitor

Abstract: Although Toll-like receptors have been widely identified and functionally characterized in mammalian models and Drosophila, the immunological function of these receptors in other insects remains unclear. Here, we explored the relevant innate immune response of Tenebrio molitor (T. molitor) Toll-3 against Gram-negative bacteria, Gram-positive bacteria, and fungal infections. Our findings indicated that TmToll-3 expression was mainly induced by Candida albicans infections in the fat bodies, gut, Malpighian tubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The expression of TmToll‐3 was induced in response to C. albicans infections within MTs. Furthermore, when TmToll‐3 was experimentally silenced, the expression of AMP genes and the associated transcription factors was considerably downregulated, particularly after exposure to E. coli (Ali Mohammadie Kojour et al 2023). In another study, the expression levels of TmToll‐7 were assessed during development and within specific tissues.…”
Section: Functions Of Toll Signaling Pathway In Insect Infectionsmentioning
confidence: 99%
“…The expression of TmToll‐3 was induced in response to C. albicans infections within MTs. Furthermore, when TmToll‐3 was experimentally silenced, the expression of AMP genes and the associated transcription factors was considerably downregulated, particularly after exposure to E. coli (Ali Mohammadie Kojour et al 2023). In another study, the expression levels of TmToll‐7 were assessed during development and within specific tissues.…”
Section: Functions Of Toll Signaling Pathway In Insect Infectionsmentioning
confidence: 99%
“…The suppression of this protein's function leads to the impairment of the larval glands' defensive capabilities [55] . Furthermore, the research conducted by Weifeng Ding et al [57] revealed that differentially expressed genes between the defensive glands and muscle tissues of B. rhynchopetera were enriched in P450 metabolism. Notably, the downstream products of the "Metabolism of xenobiotics by cytochrome P450" gene exhibit structural similarity to certain substances previously reported in the defensive secretions of B. rhynchopetera [8] .…”
Section: Go and Kegg Enrichment Analysismentioning
confidence: 99%
“…In addition, TmToll-2 expression was elevated in young larvae gut after E. coli, S. aureus , and C. albicans invasion ( 164 ). C. albicans infection in young T. molitor larvae induced TmToll-3 within the gut; however, AMP gene transcription factors were downregulated by E. coli infection ( 165 ).…”
Section: T Molitor’s Gut Immune Responsementioning
confidence: 99%
“…In addition, TmToll-2 expression was elevated in young larvae gut after E. coli, S. aureus, and C. albicans invasion (164). C. albicans infection in young T. molitor larvae induced TmToll-3 within the gut; however, AMP gene transcription factors were downregulated by E. coli infection (165). The potent production and proliferation of specialized daughter cells intestinal stem cells are crucial in gut cell self-renewal following infection (136).…”
Section: Toll Signaling Pathwaymentioning
confidence: 99%